Investment dynamics in the energy sector under carbon price uncertainty and risk aversion - Jinxi Yang; Sabine Fuss; Daniel J.A. Johansson; Christian Azar (Energy and Climate Change, 2023)

The social cost of methane - Christian Azar; Jorge García Martín; Daniel JA. Johansson; Thomas Sterner (Climatic Change, 2023)
A rapid and sustained reduction of methane emissions has been proposed recently as a key strategy to meet the climate targets of the Paris Agreement. The social cost of methane (SCM), which expresses the climate damage cost associated with an additional metric ton of methane emitted, is a metric that can be used to design policies to reduce the emissions of this gas. Here, we extend the DICE-2016R2 model so that it includes an improved carbon cycle and energy balance model as well as methane emissions, methane abatement cost, and an atmospheric methane cycle explicitly to be able to provide consistent estimations of the SCM. We estimate the SCM to lie in the range 880–8100 USD/tCH 4 in 2020, with a base case estimate of 4000 USD/tCH 4 . We find our base case estimate to be larger than the average SCM presented in other studies mainly due to the revised damage function we use. We also estimate the social cost of carbon (SCC) and find that SCM estimates are less sensitive to variations in the social discount rate than the SCC due to the relatively short lifetime of methane. Changes in the parameterization of the damage function have similar relative impacts on both SCM and SCC. Furthermore, we evaluate the ratio of SCM to SCC as an alternative metric to GWP-100 of CH 4 to facilitate tradeoffs between these two gases. We find this ratio to lie in the range 7–33 in 2020, with a base case estimate of 21, based on an extensive sensitivity analysis with respect to the discount rate, damage cost, and underlying emission scenarios. We also show that the global warming potential (GWP) and the SCM to SCC ratio are almost the same if the inverse of the effective discounting (in the social cost calculations) is equal to the time horizon used to evaluate the GWP. For comparison, the most widely used GWP, i.e., with a time horizon of 100 years, equals 27, hence in the upper range of the ratio we find using the SCM to SCC ratio.

Paris Agreement requires substantial, broad, and sustained policy efforts beyond COVID-19 public stimulus packages - Katsumasa Tanaka; Christian Azar; Olivier Boucher; Philippe Ciais; Yann Gaucher; Daniel J. A. Johansson (Climatic Change, 2022)
It has been claimed that COVID-19 public stimulus packages could be sufficient to meet the short-term energy investment needs to leverage a shift toward a pathway consistent with the 1.5 °C target of the Paris Agreement. Here, we provide complementary perspectives to reiterate that substantial, broad, and sustained policy efforts beyond stimulus packages will be needed for achieving the Paris Agreement long-term targets. Low-carbon investments will need to scale up and persist over the next several decades following short-term stimulus packages. The required total energy investments in the real world can be larger than the currently available estimates from integrated assessment models (IAMs). Existing databases from IAMs are not sufficient for analyzing the effect of public spending on emission reduction. To inform what role COVID-19 stimulus packages and public investments may play for reaching the Paris Agreement targets, explicit modelling of such policies is required.

Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: the importance of private collections - Carolin Haug; Jelle W. F. Reumer; Joachim T. Haug; Antonio Arillo; Denis Audo; Dany Azar; Viktor Baranov; Rolf Beutel; Sylvain Charbonnier; Rodney Feldmann; Christian Foth; René H. B. Fraaije; et al. (PalZ, 2020)

Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: Myanmar amber - Joachim T. Haug; Dany Azar; Andrew Ross; Jacek Szwedo; Bo Wang; Antonio Arillo; Viktor Baranov; Julia Bechteler; Rolf Beutel; Vladimir Blagoderov; Xavier Delclòs; Jason Dunlop; et al. (PalZ, 2020)

Rapamycin increases oxidative metabolism and enhances metabolic flexibility in human cardiac fibroblasts - Timothy Nacarelli; Ashley Azar; Oya Altinok; Zulfiya Orynbayeva; Christian Sell (GeroScience, 2018)

Correlations between age, functional status, and the senescence-associated proteins HMGB2 and p16INK4a - Ibiyonu Lawrence; Michael Bene; Timothy Nacarelli; Ashley Azar; Justin Z. Cohen; Claudio Torres; Gregg Johannes; Christian Sell (GeroScience, 2018)

Emission metrics and sea level rise - Erik Sterner; Daniel J. A. Johansson; Christian Azar (Climatic Change, 2014)

Valuing the non-CO2 climate impacts of aviation - Christian Azar; Daniel J. A. Johansson (Climatic Change, 2012)

The feasibility of low CO2 concentration targets and the role of bio-energy with carbon capture and storage (BECCS) - Christian Azar; Kristian Lindgren; Michael Obersteiner; Keywan Riahi; Detlef P. van Vuuren; K. Michel G. J. den Elzen; Kenneth Möllersten; Eric D. Larson (Climatic Change, 2010)

Uncertainty and learning: implications for the trade-off between short-lived and long-lived greenhouse gases - Daniel J. A. Johansson; U. Martin Persson; Christian Azar (Climatic Change, 2008)

Bury the chains and the carbon dioxide - Christian Azar (Climatic Change, 2007)

Tropical deforestation in a future international climate policy regime—lessons from the Brazilian Amazon - U. Martin Persson; Christian Azar (Mitigation and Adaptation Strategies for Global Change, 2007)

A scenario based analysis of land competition between food and bioenergy production in the US - Daniel J. A. Johansson; Christian Azar (Climatic Change, 2007)

The Cost of Using Global Warming Potentials: Analysing the Trade off Between CO2, CH4 and N2O - Daniel J. A. Johansson; U. Martin Persson; Christian Azar (Climatic Change, 2006)

Carbon Capture and Storage From Fossil Fuels and Biomass – Costs and Potential Role in Stabilizing the Atmosphere - Christian Azar; Kristian Lindgren; Eric Larson; Kenneth Möllersten (Climatic Change, 2006)

Economics and Distribution in the Greenhouse - Christian Azar (Climatic Change, 2000)

Maize landraces of the St. Lawrence-Great Lakes region of North America - Christian Azar; Diane E. Mather; Robert I. Hamilton (Euphytica, 1997)